Contract cheating: a survey of Australian university staff. Issue 11 (2nd November 2019) - Harper, Rowena; Bretag, T.; Ellis, C.; Newton, P.; Rozenberg, P.; Saddiqui, S.; van Haeringen, K.
ABSTRACT: If media reports are to be believed, Australian universities are facing a significant and growing problem of students outsourcing their assessment to third parties, a behaviour commonly known as 'contract cheating'. Teaching staff are integral to preventing and managing this emerging form of cheating, yet there has been little evidence-based research to inform changes to their practice. This paper reports on the findings of a large-scale survey of teaching staff in Australian universities on the topic of contract cheating. It investigated staff experiences with and attitudes towards student cheating, and their views on the individual, contextual and organisational factors that inhibit or support efforts to minimise it. Findings indicate that contract cheating could be addressed by improving key aspects of the teaching and learning environment, including the relationships between students and staff. Such improvements are likely to minimise cheating, and also improve detection when cheating occurs.